The Effect of Sleep Quality on Blood Pressure: Literature Review - Setiawan, Arif; Sulistyani, S; Herawati, Erna; Basuki, Sri Wahyu (Prosiding University Research Colloquium, 2022)
Background : Hypertension generally affects adults to the elderly. In many countries, the diagnosis of hypertension is made at a systolic blood pressure (SBP) of at least 140 mmHg, and a diastolic blood pressure of at least 90 mmHg. Several studies have reported correlations between sleep duration and chronic conditions, including type 2 diabetes, obesity, atherosclerosis, and high blood pressure. Purpose : Knowing the effect of sleep quality on blood pressure. Method : This Research is a literature review type. Literature review data was collected by browsing published article on pubmed, science direct, and google scholar databases. Result : Search results obtained (1297) from Pubmed database, (980) articles from Google Scholar, (1001) from Science Direct articles. Most (11/12) studies show that sleep quality and sleep duration have an effect on systolic blood pressure. Conclusion : Poor sleep quality and sleep duration of less than 7 hours, especially less than 5 hours are at risk of increasing the incidence of hypertension.